Spinal myoclonus induced by contrast material: an alternative explanation. - Heyman, S N; Greenfeld, Z; Behar, M; Mogle, P; Brezis, M (American Journal of Neuroradiology, 1989)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf